CORROSION OF AMALGAMS IN ORAL CAVITY (Journal of Engineering, 2011)
This paper is a study of the effect of natural saliva (oral cavity) and a fluoride mouthwash on dentalamalgams .Two types electrodes were made the first was of a high copper amalgam while the second wasmade from a low copper amalgam. They were immersed in two types of electrolytes for twelve hours and the whole galvanic cell was connected to a computer via a potentiosat. Their corrosion currents, corrosionvoltage and corrosion resistance was recorded and compared to find which medium that is usually has themost severe effect on the amalgams corrosion.